Industrial Policy and Sustainable Growth (Sustainable Development, 2018)
This volume looks at the critical issues of industrial policy and sustainability. It assesses the gap between how developed and developing countries have integrated sustainability issues in their industrial policies, and how they should have ideally done so. The book looks at the specific issues of middle income trap, levels of industrialization and the distribution of manufacturing activities among nations, and presents analysis of sector and country specific policy case studies in areas such as health, energy, medical devices, aviation, automobile manufacturing. The volume also examines trade policies and their impact on industry and environment, and elaborate on how industrial policies involve selective direct and indirect sectoral policies which play a role in assisting policy makers manage objectives of catch up and sustainability.